Environmental protection as a fundamental part in tourism development and insurance industry commitment to suporting it - Vasileska, Larisa (Array, 2008)
Abstract: In recent decades, tourism has become a full-fledged industry contributing significantly to the economic and social development of a large number of countries. In order to guarantee sustainable development of the environment for the future generations, insurers are ready to face with the new challenge as the investment in the sustainable development is very great